Sartre, The Condemned of Altona and the Critique of Dialectical Reason-to-come: Insanity or Bad Faith Running Away with Itself?. Issue 48 (3rd April 2017) - Mirvish, Adrian
ABSTRACT: What for Sartre happens when bad faith goes so deep that one is no longer master of it? In The Condemned of Altona, Franz Gerlach, after an initial show of resistance, joins the Nazi cause and tortures prisoners of war in his charge. Fleeing home from Russia at the war's end, he sequesters himself in the attic of the family mansion and attempts to absorb the guilt of the twentieth century by frantically arguing his case before a tribunal of scuttling crabs. What does Sartre's portrayal of hallucination tell us about the human condition and is it the result of insanity? As a harbinger for the Critique of Dialectical Reason (CDR), Sartre's ontology has shifted away from an emphasis on human isolation and absolute freedom to a concern with how behaviour, even of an irrational kind, is a profound reflection of one's place in a social hierarchy. Also a reflection of a CDR-type approach, Sartre's views change regarding the status of truth and interpersonal relations. For while someone like Nausea 's Roquentin exhibits a redemptive value through introspection, fantasy and private experience, Franz's behaviour points to a repeated failure to deal with social reality and the associated attempt to redeem his own existence by acting authentically towards others.